Comparative analysis of the GATA transcription factors in seven Ipomoea species - Si, Zengzhi; Guo, Jiuting; Ji, Zhixin; Men, Fengrui; Wang, Weicao (Frontiers in Plant Science, 2025)
The GATA transcription factors regulate plant growth, development, and stress responses, but our knowledge of their functions in sweetpotato and related Ipomoea species remains limited. Through analytical methods of bioinformatics, this study identified 410 GATA genes across seven sequenced Ipomoea species: sweetpotato (158), I. trifida (54), I. triloba (62), I. nil (39), I. purpurea (32), I. cairica (32), and I. aquatica (33). Phylogenetic analysis revealed that these GATA genes clustered into four distinct subfamilies (I-IV). Chromosomal mapping showed an uneven distribution pattern, with complete absence of GATA genes on certain chromosomes in each species. Duplication analysis indicated differential expansion mechanisms: tandem duplications primarily drove GATA gene expansion in I. triloba, I. trifida, and I. nil, whereas segmental duplications were predominant in sweetpotato and I. cairica. Promoter analysis identified multiple stress-responsive cis-regulatory elements, including ABRE, ARE, CGTCA-motif, GC-motif, LTR, MBS, TCA-element, TC-rich repeats, and TGACG-motif. Expression profiling under various stresses (salt, drought, Ceratocystis fimbriata and Ditylenchus destructor) detected 29–60 differentially expressed GATA genes (DEGs). Three representative DEGs (IbGATA33, IbGATA38, and IbGATA126) were validated by qRT-PCR, with results corroborating the transcriptome data. This study may contribute to further understanding of the evolution and function of GATA genes among the Ipomoea species, including sweetpotato.